Amperometric Detection of Bacillus anthracis Spores: A Portable, Low-Cost Approach to the ELISA - Gabriel D. Peckham; Brian E. Hew; David F. Waller; Charlie Holdaway; Michael Jen (International Journal of Electrochemistry)
Antibody-based detection assays are generally robust, a desirable characteristic for in-the-field use. However, to quantify the colorimetric or fluorescent signal, these assays require expensive and fragile instruments which are ill-suited to in-the-field use. Lateral flow devices (LFDs) circumvent these barriers to portability but suffer from poor sensitivity and subjective interpretation. Here, an antibody-based method for detecting Bacillus anthracis spores via amperometric signal generation is compared to ELISA and LFDs. This amperometric immunoassay uses antibody conjugated to magnetic beads and glucose oxidase (GOX) along with the electron mediator 2, 6-dichlorophenolindophenol (DCPIP) for production of a measurable current from a 0.4 V bias voltage. With similar sensitivity to ELISA, the assay can be completed in about 75 minutes while being completely powered and operated from a laptop computer. Immunoassay amperometry holds promise for bringing low-cost, quantitative detection of hazardous agents to the field.